The Wiley-Blackwell companion to major social theorists - Ritzer, George, Ed; Stepnisky, Jeffrey, Ed (Blackwell companions to sociology ;, 2011)
"Reflecting emerging research and ongoing reassessments of social theory, The Wiley-Blackwell Companion to Major Social Theorists offers significant updates and revisions to the original Blackwell Companion published a decade ago. Volume I: Major Classical Theorists presents 18 comprehensive essays on social theorists writing in the classical tradition, more than half all-new for this Companion, written by some of the most eminent contemporary scholars in their field. In addition to detailing the make-up and development of specific social theories, each essay places the theorist and their ideas in personal, social, and historical context; and integrates the most current scholarship to offer assessments as to their continuing relevance. Well-known theorists such as Comte, Spencer, Marx, Durkheim, Weber, Simmel, Mead, Schutz, and Parsons are represented, as well as theorists historically excluded from the sociological canon, including Ibn Khaldun, Martineau, Gilman, and Du Bois. Other essays consider a set of classical theorists chosen for their particular relevance to contemporary theory: de Tocqueville on democracy, Schumpeter on capitalism, Mannheim on the sociology of knowledge, Veblen on consumer society, and Adorno on cultural theory. Edited by one of the most renowned figures in social theory, the Wiley-Blackwell Companion is an indispensable resource and reference to the life and times of the classical thinkers and their relevance to modern theorists and today's social world"--